Orientasi Manajemen Pendidikan: Penguatan Kualitas Pengajaran Tingkat Sekolah Menengah Atas di Kota Makassar - Erni Ratna Dewi (Phinisi Integration Review, 2022)
This research to describes and analyzes the orientation of education management in strenghtening teaching quality according to planning, organizing, implementing and monitoring activities. This research approach uses a qualitative approach. Data obtained through observation and documentation. Data nalysis was carried out through data reduction, data presentation and data verification. The results of this study are orientation of education management on planning activities for strengthening the quality of teaching is carried out at the end of each year, starting with planning aspects of the curriculum, students, educators and education staff, as well as infrastructure. The orientation of education management is on organizing activities in strengtening the quality of organized teaching, starting from organizing the overall development of the school then practically carried out by the principal assisted by the deputy principal as well as teachers and administration. The orientation of education management is on its implementation activities by paying attention to input from school programs in the field of curriculum aspects, students, educators and education staff, as well as infrastructure. The teacher carries out the learning process according to the initial activities, core and closing activities according to the plan to achieve output according to curriculum standards. The orientation of education management on supervisory activities is carried out by the principal in collaboration with supervisors from the education office in monitoring teachers on the implementation of learning the principal is assisted by the vice principal.